Персональные компьютеры пер. с болг. - Боянов К. Л. Кирил Л.; Гетов В. С. Владимир С.; Вецев Н. Г. Никола Г.; Илиев М. С. Мирослав С.; Арабаджийски К. С. Кръстю С.; Мачев С. С. Стефан С.; Комарницкий В. А. (Москва, Машиностроение, 1989)
Исключено из фонда НТБ ТПУ